Managerial styles of small business owners: a study based on the organizational life cycle and on concepts concerning managers' functions and roles - Oliveira, Jair de; Escrivao Filho, Edmundo; Nagano, Marcelo Seido; Ferraudo, Antonio Sergio [UNESP] (Fund Escola Comercio Alvares Penteado-fecap, 2015)
Objective - To identify the managerial styles of small business managers at every stage of the organizational life cycle, considering managers' work, approaches to process and roles. Methodology - This research was considered of applied nature, of quantitative approach, as descriptive from the point of view of the objectives, and as a survey because of its technical procedures. Seventy companies belonging to the metallurgical-mechanical industry in Sao Paulo, Brazil, took part in the study. Theoretical framework - It was found that the owner of small businesses change the valuation of the functions and of the roles of the administrator, according the company's development stage. Three management styles have been identified as the most prominent of small business owner, considering the organizational life cycle. Findings - It was found that the owner of small businesses change the valuation of the functions and of the roles of the administrator, according the company's development stage. Three management styles have been identified as the most prominent of small business owner, considering the organizational life cycle. Contributions - This research presents evidence that there is a relationship between the functions and roles of managers (theorized for large companies) and the work carried out by small business leaders, as well as the feasibility of researching the functions and roles of managers alongside each other, rather than individually, as most other studies do.
Keywords: Small business manager; Organizational life cycle; Manager's work; Process approach; Roles approach